Corruption the new corporate challenge - Kochan, Nick; Goodyear, Robin (Palgrave Macmillan, 2011)
The dangers of involvement in corruption need to be embedded in corporate strategy. Companies' response to these dangers must also be reflected in their practices, particularly if operating outside its own borders. This book guides managers through the complexity of bribery issues with advice on how to implement anti-corruption strategies